Adaptation to raw materials intra-variability: Examples from three Middle Palaeolithic surface stations of the Hérault Valley, France (Les Geissières, Saint-Saturnin and Camillo). (2021) - , Cyrielle Mathias; Bourguignon, Laurence; Ivorra, Jérôme; Barsky, Déborah; Grégoire, Sophie; Viallet, Cyril
No abstract available